EFEKTIVITAS SENYAWA ANTIINFLAMASI DAN ANTIBAKTERI PADA RIMPANG JAHE (ZINGIBER OFFICINALE R.) - Priscinya Christiana Debora; Anggi Ayu Pratama; Tiwi Ambarati; Salsabila Granadha; Siti Nuriah (HSG (Health Science Growth) Journal, 2021)
Natural ingredients are often used by the community as alternative medicine. Natural materials that are widely used are plants because they are affordable, easy to obtain, and easy to make. Ginger (Zingiber officinale R.) The content of secondary metabolites in ginger, especially essential oils, flavonoids, phenols, and terpenoids, can be useful for reducing inflammation and inhibiting bacterial growth. The method used in this article is based on a study of the national journal literature. The results of the literature study showed that the ginger plant has pharmacological activity as anti-inflammatory and antibacterial. Key word : medicinal plants, extracts, pharmacological activity, ginger.